ANGUINID NEMATODE SPECIES IN MANIPUR - MOHILAL, N.; ANANDI, Y.; DHANACHAND, CH. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2001)
<span style="color: #000000; font-family: Roboto, sans-serif; font-size: 13px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Two species belonging to the family Anguinidae of class Nematoda are reported. They are Ditylenchus microdens Filipjev, 1934 and Pseudhalenchus anchilisposomus Tarjan, 1958. They are reported for the first time from Manipur.